Rancang Bangun Aplikasi Pengelola Pada Toko Vape Berbasis Visual Studio - Febianti, Nabila Putri; Faadihilah, Daffa Bayu; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
Manual management of vape stores often faces challenges in recording inventory and transactions, leading to data errors and operational inefficiencies. This research aims to develop a vape store management application using Visual Studio with a MySQL Server database to optimize product data and sales transaction management. The system development method follows the waterfall model, encompassing requirements analysis, design, implementation, and testing phases. The application was developed using Visual Basic.NET and MySQL Server, featuring key functionalities such as product master management, automated sales transaction modules, and sales reporting based on specific periods. Testing results show that the application functions optimally in managing inventory and generating accurate sales reports. The implementation of this application improves the operational efficiency of vape stores by reducing recording errors and speeding up customer service.